2017
DOI: 10.1177/0004865817717055
|View full text |Cite
|
Sign up to set email alerts
|

Crime prevention and reduction programs: How does knowing about community initiatives moderate attitudes towards criminal victimisation?

Abstract: The current study examines the association between fear of crime and awareness of community programs designed to prevent or reduce crime and social disorder. Data were collected from a community survey of household residents living on the Gold Coast of Australia (N ¼ 713). Results indicate that those reportedly aware of community initiatives, fear property crime and crimes against persons differently than those reportedly unaware of them. For fear of personal victimisation, awareness of crime prevention progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Previous literature, which did not include these three types of victimization, presents mixed results. Some studies found that violent victimization is not significantly associated with FOC (H. Lee et al., 2020), while others stated that FOC is more likely to appear when individuals are asked to reflect on crimes against persons (Chataway & Hart, 2017). In addition, a recent study found that direct and indirect victimizations affect FOC (Hernández, 2017), while H. Lee et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous literature, which did not include these three types of victimization, presents mixed results. Some studies found that violent victimization is not significantly associated with FOC (H. Lee et al., 2020), while others stated that FOC is more likely to appear when individuals are asked to reflect on crimes against persons (Chataway & Hart, 2017). In addition, a recent study found that direct and indirect victimizations affect FOC (Hernández, 2017), while H. Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…First, do all types of crime victimization (violent, body-aimed, and indirect) affect FOC equally? Although there is plenty of evidence that victims of crime tend to have higher levels of FOC (Farrall et al., 2007; Wilcox & Land, 1996), there are only a few (Chataway & Hart, 2017). More specifically, do violent victimization (committed with arms), body-aimed victimization (physical or sexual abuse from a member of their household, and sexual offenses), and indirect victimization (crimes suffered by others at home) influence FOC in a different way?…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation